Implementasi Pendidikan Karakter Melalui Program Ko-Kurikuler Dalam Mewujudkan Karakter Religius Siswa - Bahrudin Bisri, M. Didin (Menara Tebuireng, 2024)
Abstract— This study aims to explore the implementation of character education through co-curricular programs in shaping the religious character of students at MAN 1 Jombang. The research method used is a case study with a qualitative approach. Data were collected through observations, interviews, and document analysis. The results show that co-curricular programs, such as morning activities, congregational prayers, recitation of prayers, and other religious activities, have had a positive impact on training discipline, religious awareness, and moral values among students. However, there are still some obstacles in the implementation of the program, such as limited time, the number of supervising teachers, and parental involvement. Nevertheless, efforts to overcome these obstacles have been made by involving innovative teaching strategies and improving coordination between teachers and educational staff. In conclusion, character education is an essential aspect of Islamic education that requires commitment and cooperation from all relevant parties to continuously improve the quality of character education in the school to create a generation of high-quality and morally upright individuals. Keyword: character education, co-curricular programs, religious character